MANAGEMENT SUPPORT AND EMPLOYEE MINDSET IN IMPLEMENTING SUSTAINABLE LIVING CULTURE IN THE PLN NUSANTARA POWER ENVIRONMENT - Hilda Iriany; Iskandarini; Yeni Absah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
In order to maintain environmental sustainability and minimize the negative impacts of human activities on the earth, PLN Nusantara Power has implemented strategic steps to build a sustainable living culture. This effort is carried out as part of the company's commitment to achieving sustainability goals and carrying out environmental responsibilities. Challenges in implementing a sustainable living culture are often influenced by an ingrained organizational culture, which may be resistant to change or innovation. Top management support is key to overcoming these obstacles. Management must provide adequate facilities, provide rewards, and provide ongoing training to encourage change. The data analysis technique in this study was carried out with classical assumptions and multiple linear regression tests. The results of this study indicate that the Management Support Variable of 0.0264 and the Employee Mindset Variable of 0.556 show a positive and significant influence on the sustainable living culture. These results indicate that a positive employee mindset that is in line with the principles of sustainability is one of the important keys in creating a more environmentally friendly and sustainable work environment. Simultaneously, the two independent variables, namely management support and employee mindset, together have a positive and significant influence on the sustainable living culture.